(untitled) (MAUSAM, 1983)
The movement of cold fronts with associated westerly waves in the lower troposphere across southern Africa and adjoining southwest Indian Ocean during the months of May and June has been examined in relation to the onset of southwest monsoon over the west coast of India. The study is based on satellite pictures for the years 1971 and 1972 and on extensive MONEX data for the year 1979, It has been found that the passage of deep cold fronts across southern Africa and adjoining oceanic areas exercise marked influence on the strength of the cross equatorial flow which in turn leads to the organisation and intensification of ITCZ and its northward advancement causing the onset of the southwest monsoon. This association can be used as an aid in forecasting the onset of southwest monsoon along the west coast of India 4 to 7 days in advance.